2008
DOI: 10.7773/cm.v34i1.1232
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the angular angel shark Squatina guggenheim (Chondrichthyes: Squatinidae) off Patagonia (Argentina, southwestern Atlantic)

Abstract: The reproductive biology of the angel shark Squatina guggenheim was described based on 584 animals sampled in the San Matías Gulf, Argentina, between January and December 1996. Both sexes of S. guggenheim reached similar total length and matured at similar sizes (between 73 and 76 cm total length). In males, testes were paired and showed diametric development. Adult males were predominant in the austral autumn and winter, and were capable of mating all year round. In females, only the left ovary was functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
(89 reference statements)
1
18
0
2
Order By: Relevance
“…Females were larger than males; sexual dimorphism has previously been reported among squatinids (Capapé et al, 1990(Capapé et al, , 2002(Capapé et al, , 2005Awruch et al, 2000;Colonello et al, 2007). This condition could be an adaptation to the greater energy demands of their viviparous reproductive mode (Goodwin et al, 2002).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Females were larger than males; sexual dimorphism has previously been reported among squatinids (Capapé et al, 1990(Capapé et al, , 2002(Capapé et al, , 2005Awruch et al, 2000;Colonello et al, 2007). This condition could be an adaptation to the greater energy demands of their viviparous reproductive mode (Goodwin et al, 2002).…”
Section: Discussionmentioning
confidence: 55%
“…In California, size at maturity was estimated at 90-100 cm L T (Natanson & Cailliet, 1986), suggesting different life-history parameters for these two S. californica populations. Latitudinal differences between sexes in L T50 have also been observed for Squatina guggenheim Marini 1936 (Awruch et al, 2000;Colonello et al, 2007). The differences have been explained by the fact that Squatina have low dispersal capability, making identification of differences in life-history parameters at small geographic scales possible (Colonello et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Despite the reproductive behaviour of the angelshark being poorly understood, Narvaez (2013) and Osaer (2009) have also indicated that active males were predominantly found during winter and that the pupping season started in spring at Gran Canaria Island, as has been demonstrated here. Sexual segregation, either seasonal or spatial, has also been observed for other species of the same genus, including Squatina californica (Pittenger, 1984), Squatina tergocellata (Bridge, Mackay, & Newton, 1998) and Squatina guggenheim (Awruch, Nostro, Somoza, & Di Giacomo, 2008). For example, similar to S. squatina, adult S. guggenheim females migrate to shallow coastal areas (< 40 m depth) to breed (Vooren & Da Silva, 1991).…”
Section: Species Distribution Modelling (Sdm)mentioning
confidence: 91%
“…Since then, studies on distribution, biology and commercial exploitation have been carried out on several fish species (Di Giácomo, 1992;Di Giácomo & Perier, 1991;1996;2009;Van der Molen et al, 1998;Awruch et al, 2008;Perier et al, 2010;Coller et al, 2011;Estalles et al, 2011). However, basic information such as species composition has remained unpublished.…”
Section: Introductionmentioning
confidence: 99%